BIOACTIVE COMPOUND ANALYSIS AND ANTIOXIDANT ACTIVITY OF ENDOPHYTIC BACTERIAL EXTRACT FROM ADHATHODA BEDDOMEI - Y, Swarnalatha; Saha, Bhaswati; Choudary y, Lokeswara (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objectives: The endophytic bacteria Lactobacillus sp. has been isolated from the tissues of plant leaves. The bacterial strains were grown in nutrient broth at 37Â°C for 5 days. To isolate the bioactive compounds, the culture was grown in a broth and the culture broth was centrifuged and the supernatant was collected. Methods: Solvent-solvent method was applied to extract the bioactive compounds. The antioxidant activity was evaluated with the help of 1,1-diphenyl -2-picrylhydrazyl radical scavenging activity. Results: The qualitative analysis of extracts indicated presence of carbohydrates, tannins, saponins, alkaloids, glycosides, proteins, amino acids, and saponins. Flavonoids and anthocyanins were showed negative results, the quantitative analysis of the phenolic compounds showed the presence of 0.67 mg/ml. The inhibitory concentration 50 value for antioxidant activity was 35 Î¼g/ml. Conclusion: The antioxidant activity is due to the presence of different bioactive, and the high levels of phenolic compounds may be responsible for antioxidant activity. Keywords: Lactobacillus sp., Antioxidant activity, Endophytic bacteria, Phenolic compounds.